Hubungan Status Gizi Dengan Kejadian Infeksi Saluran Pernapasan Akut (ISPA) Pada Balita Di Puskesmas Mekarwangi Garut Tahun 2018 - Sulastini Sulastini; Sri Yekti Widadi; Desi Sentia; Bambang Aditya Nugraha (LPPM STIKES Guna Bangsa, 2019)
Acute respiratory tract infections is an acute infection caused by viruses, fungi and bacteria. Acute respiratory tract infections cases in Indonesia still rank first with a prevalence of 25% with malnutrition morbidity of 14.9%. In Garut District, the highest incidence of ARI was in Mekarwangi Health Center as many as 8004 cases and in 1840 children under five. While the prevalence of malnutrition or (thin) as many as 104 cases and 1 case of malnutrition. Nutritional status is a state of the body as a result of food consumption and use of nutrients. Differentiated between thin nutritional status, very thin, normal nutrition and fat nutrition. Nutritional status is one of the factors that play an important role in the health of children under five. If the nutritional status of under-fives or (underweight) toddlers will be susceptible to diseases, especially infectious diseases. The general objective of this study was to determine the relationship of nutritional status with the incidence of ARI in infants in Mekarwangi Garut Health Center in 2018. The type of research used was descriptive correlative, with a case control approach, a sample of 114 respondents divided into 57 case groups and 57 control groups. bivariate test analysis using chi-square. The results of the research on the nutritional status of most underweight children and half of children under five experienced acute respiratory tract infections. Conclusion there is a relationship between nutritional status with acute respiratory tract infections in infants in Mekarwangi Garut Public Health Center in 2018. It is recommended that health workers improve counseling to the public about the factors that affect acute respiratory tract infections in order to be able to overcome and prevent, especially the problem of nutrition improvement.